2020
DOI: 10.1590/fst.13219
|View full text |Cite
|
Sign up to set email alerts
|

Screening and identification of bacteriocin-like inhibitory substances producing lactic acid bacteria from fermented products

Abstract: Lactic acid bacteria (LAB) are Gram-positive rods or cocci, aerotolerant, homofermentative or heterofermentative and lactic acid producers. LAB can produce organic substances that are responsible for the unique aroma (Caplice & Fitzgerald,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 38 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…The centralized management of multiplexed devices implemented in our hospital according to relevant specifications has effectively improved some problems and achieved good results. However, with the continuous progress of work, it is found that its shortcomings are more and more distinct (Wang & Wei, 2019;Choeisoongnern et al, 2020). The centralized management involves a lot of contents and objects, and the work is complex, especially for the reusable equipment, there is usually a more complex cleaning, disinfection and inspection procedure between the recycle and reuse.…”
Section: Discussionmentioning
confidence: 99%
“…The centralized management of multiplexed devices implemented in our hospital according to relevant specifications has effectively improved some problems and achieved good results. However, with the continuous progress of work, it is found that its shortcomings are more and more distinct (Wang & Wei, 2019;Choeisoongnern et al, 2020). The centralized management involves a lot of contents and objects, and the work is complex, especially for the reusable equipment, there is usually a more complex cleaning, disinfection and inspection procedure between the recycle and reuse.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of temperature was assessed by exposing the substance to various temperatures (30-90 °C) for 15 minutes, and the pH effect was evaluated by adjusting the pH of the substance (1.5-3) in nutrient broth. Enzyme controls were prepared using phosphate buffer to purify bacteriocinlike inhibitory substances, as mentioned (Choeisoongnern et al, 2019). The potency of the substance was also monitored over several weeks against sensitive indicators using the Well-diffusion method.…”
Section: Characterization Of Bacteriocin-like Inhibitory Substance (B...mentioning
confidence: 99%
“…Similarly, Leite et al [20] described BLIS produced by Bacillus cereus LFB-FI-OCRUZ 1640, with activity against Listeria monocytoges and other Bacillus species in pineapple pulp and can be used as a potential food bio preservative. Also, Choeisoongnern et al [21] reported that BLIS produced by Pediococcus pentosaceus, and Enterococcus faecium from fermented food inhibits the growth of Carnobacterium maltraromaticum, Candida albicans, Listeria ivanovii, Listeria innocula, Pseudomonasc aeruginosa, Streptococcus mutans, and S. aureus. More recently, Pircalabioru et al [22] comprehensively reviewed bacteriocins' potential as an antimicrobial agent against infections mainly due to resistant pathogens i.e., MRSA.…”
Section: Ribosomally Synthesized Antimicrobial Peptides (Bacteriocins) and Bacteriocin-like Inhibitory Substances (Blis)mentioning
confidence: 99%